Technology and the Future of Work - Peralta-Alva, Adrian (IMF Working Papers; Working Paper ;, 2018)
This paper uses a DSGE model to simulate the impact of technological change on labor markets and income distribution. It finds that technological advances offers prospects for stronger productivity and growth, but brings risks of increased income polarization. This calls for inclusive policies tailored to country-specific circumstances and preferences, such as investment in human capital to facilitate retooling of low-skilled workers so that they can partake in the gains of technological change, and redistributive policies (such as differentiated income tax cuts) to help reallocate gains. Policies are also needed to facilitate the process of adjustment.